ESTIMATION OF HYDROGENERATOR ROTOR DYNAMIC THERMAL MARGINE - Klasnić, Ilija G; Belonić, Dragan; Janda, Žarko; Dragosavac, Jasna; Ćirić, Zoran (Proceedings, Electrical engineering institute "Nikola Tesla", 2022)
Field winding temperature of the synchronous generator is one of the operating limits indicated in the generator PQ diagram. Therefore as accurate as possible information about its value is of great importance. It can be measured directly using built-in temperature sensors or determined indirectly. With the increasing penetration of renewable energy sources into the high-voltage transmission system, there are fundamental changes in the way conventional units work, including hydrogenerators. They are facing operating modes characterized by rapid load changes and an increased number of start-stop cycles. This mode of operation causes additional thermal stress on parts of the hydrogenerator, including the rotor. In order to be able to respond to new demands that they are facing, it is necessary to know the thermal capacity of the rotor and its influence on the dynamic hydrogenerator PQ diagram.
Keywords: hydrogenerator, thermal capacity, field winding thermal time constant, temperature of field winding